FIQH TOLERANSI:PANDANGAN SANTRI MA’HAD ALY SITUBONDO TENTANG PRAKTEK TOLERANSI MUSLIM TERHADAP NON MUSLIM - Aziz, Abdul (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2018)
Religious differences are often being the cause or source of a dispution. Evidently from some occurred events, such as the Bali Bombing 1 and 2, rebellion at Poso, and the others. These events have implications for a negative view of Islam. In case Islam already has a jargon rahmatan lil alamin. And to display the image of rahmatan lil alamin santri Mahad Aly Sukorejo Situbondo discuss some issues about the practice of Muslim tolerance to non-Muslims contained in bulletin Tanwirul Afkar. This study focuses on two things, santri Mahad Aly Situbondo opinion about the practice of tolerance and their istinbath method in digging the law. In conclusion, they prefer the opinions of weak minority clerics in order to practice tolerant attitudes. Whereas in exploring the law they are based on the Quran, hadith, and other arguments in addition to the opinions of the Fiqh scholars.